2007
DOI: 10.1007/s11422-006-9035-8
|View full text |Cite
|
Sign up to set email alerts
|

Communication about science in a traditional museum: visitors’ and staff’s perceptions

Abstract: This study investigated visitors' and staff's perceptions about the communication of science in a traditional natural history museum. The research examined the science-related outcomes for adult visitors and explored visitors' and staff's ideas of science and how it is portrayed at the museum. Data were collected by questionnaire and interview from 84 staff and 102 visitors. Both groups held positive views about science, its importance and the need for everyone to understand it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
(28 reference statements)
0
9
0
1
Order By: Relevance
“…In agreement with Rennie and Williams (2006), teacher education in the Museum now affords teachers gaining an understanding of ''science as a process of building explanations about natural phenomena,'' (para 3), however it falls short on presenting science as culturally contextualized. Nonetheless this way of thinking about teacher education in the Museum enables the teacher to move from being a passive recipient of the Museum's resources/knowledge to an active participant in the Museum's education community.…”
Section: Education In the Museum: The Present Decadesmentioning
confidence: 91%
See 1 more Smart Citation
“…In agreement with Rennie and Williams (2006), teacher education in the Museum now affords teachers gaining an understanding of ''science as a process of building explanations about natural phenomena,'' (para 3), however it falls short on presenting science as culturally contextualized. Nonetheless this way of thinking about teacher education in the Museum enables the teacher to move from being a passive recipient of the Museum's resources/knowledge to an active participant in the Museum's education community.…”
Section: Education In the Museum: The Present Decadesmentioning
confidence: 91%
“…Winford (2003) describes ideologies of language as having the ''power not only to shape the way people talk and interact generally, but also to naturalize relations of power and privilege'' (p. 28)-this can extend to the ideologies of science as taught in schools and displayed in museums. Rennie and Williams (2006) define cultural science literacy as ''knowing something about science as a major human achievement'' (para 4). As a major human achievement, science literacy should also emphasize that science is culturally bound, produced by different cultures (not only the West), and in different historical contexts.…”
Section: Creolizing Sciencementioning
confidence: 99%
“…Außerschulische Lernorte setzen hier an und versuchen dieser geringen Attraktivität des naturwissenschaftlichen Unterrichts entgegenzuwirken und den schulischen Unterricht bei der Entwicklung einer naturwissenschaftlichen Grundbildung zu unterstützen (vgl. Rennie & Williams, 2006;Neubauer, 2015). Durch einen praxisorientierten, offeneren Zugang sollen außerschulisch die Motivation sowie das Interesse gefördert und dazu anregt werden, sich mit naturwissenschaftlichen Themen zu befassen (Hobbensiefken, 2010).…”
Section: Herausforderung Interesse Und Motivation Zu Wecken Und Zu Haltenunclassified
“…These conventional one‐way communications place the curator in a position of power, selecting the objects and writing the labels in ways that dictate meaning based on their ‘vision’ of what should be learned (McLean ). Studies have suggested visitors to these types of museums do not feel their views of science change after a visit, nor do they report that the experience stimulates them to think critically about science (Rennie and Williams ). It would seem that this approach may neglect opportunities to more widely ‘engage’ with visitors (House of Lords ; Miller ).…”
Section: The Themed Gallery Paradigmmentioning
confidence: 99%